Gas-sensing properties of zinc ferrite nanoparticles synthesized by the molten-salt route - Darshane, Sonali L.; Deshmukh, Rupali G.; Suryavanshi, Shankar S.; Mulla, Imtiaz S. (Journal of the American Ceramic Society, 2008)
Zinc ferrite (ZnFe2O4) nanoparticles have been synthesized at 700 degrees C using sodium chloride as a growth inhibitor. Single-phase formation of spinel zinc ferrite having crystallite size in the range of 15-20 nm was observed by XRD and confirmed by TEM. In the present work, the gas-sensing properties of these zinc ferrite nanoparticles toward ethanol, LPG, H-2, NOx. SOx, and H2S have been studied. It was found that they exhibit excellent selective sensitivity toward 200 ppm of H2S at the operating temperature of 250 degrees C, and thus this nanosized ferrite is expected to be useful in an industrial application as a potential H2S gas sensor.

Preparation of ferroelectric CaBi(4)Ti(4)O(15) powders from novel hydroxide precursors - Deshmukh, Rupali G.; Vaishampayan, Mukta V.; Darshane, Sonali L.; Mulla, Imtiaz S.; Gaikwad, A. B.; Rao, N. Kotaserwara; Ravi, V. (Materials Letters, 2008)
Ferroelectric CaBi(4)Ti(4)O(15) (CBT) powders were prepared for the first time from their respective hydroxides. Commercially purchased Ca(OH)(2) is mixed thoroughly with freshly prepared Bi(OH)(3) and Ti(OH)(4) in stoichiometrie ratio and heated at different temperatures ranging from 100 to 600 degrees C. The CBT phase found to be formed at 500 degrees C by the X-ray diffraction studies. This is the lowest temperature so far reported in the literature for the formation of CBT phase. The advantage of this method is that it also avoids the formation of calcium carbonate phase during synthesis. The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD) method. The average particle size and morphology were studied by scanning electron microscopy (SEM) technique. (c) 2007 Elsevier B.V All rights reserved.
Keywords: CaBi(4)Ti(4)O(15); Ceramics; Chemical synthesis; Electron microscopy; Oxides; X-ray methods

Nanostructured nickel ferrite: a liquid petroleum gas sensor - Darshane, Sonali L.; Suryavanshi, S. S.; Mulla, Imtiaz S. (Ceramics International, 2009)
The present investigation deals with the synthesis of nanostructured nickel ferrite (NiFe(2)O(4)) and their liquid petroleum gas-sensing characteristics. The 15-20 nm size nickel ferrite has been synthesized at 700 degrees C by a simple molten-salt route using sodium chloride as grain growth inhibitor. These nanoparticles exhibit significantly high response towards liquid petroleum gas (LPG) in comparison with ethanol vapor, hydrogen sulfide, ammonia and hydrogen. The gas response towards various gases at their 200 ppm concentrations is investigated at 200-450 degrees C. Different characterization techniques have been employed, such as differential thermal analysis, X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and high resolution transmission electron microscopy (HRTEM) to study the crystallite size, structure and morphology. The results suggest possibility of utilization of the nanostructured nickel ferrite, without addition of any precious metal ion, as the LPG detector. (c) 2008 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Ferrites; nanomaterial; Sensor; Spinels

Influence of palladium on gas-sensing performance of magnesium ferrite nanoparticles - Darshane, Sonali L.; Mulla, Imtiaz S. (Materials Chemistry and Physics, 2010)
Commercial ferrites with high densities are mostly used in the electromagnetic devices, which require high temperature synthesis. In this article the gas-sensing characteristics of pure and Pd-doped MgFe(2)O(4) powder has been discussed. The synthesis has been carried out by using a simple molten salt method. This method facilitates rapid synthesis at comparatively lower temperature enabling formation of nanostructures, suitable for the gas-sensing application. Various physicochemical techniques have been used for the characterization of samples. X-ray diffraction analysis confirmed the single-phase formation of pure and Pd-doped MgFe(2)O(4) having crystallite size 15-20 nm. Pure MgFe(2)O(4) showed highest responses towards liquid petroleum gas (LPG) at 350 degrees C while, on doping with Pd the highest response shifted towards lower operating temperature of similar to 200 degrees C. Pure MgFe(2)O(4) exhibited some response towards 200 ppm of LPG which markedly increased on doping of palladium (Pd). The probable mechanism is proposed to explain the selective response towards LPG. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Doping; Ferrite; LPG sensor; Molten salt synthesis; Nanostructures